1986
DOI: 10.1007/bf00441868
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of plasma lipids in Nigerian children with protein-energy malnutrition

Abstract: The fatty acid (FA) composition of the main plasma lipids was analysed in eight well-nourished, generally healthy Nigerian children aged 14.1 +/- 7.2 months and in 17 malnourished children (8 marasmus, 9 kwashiorkor) aged 14.6 +/- 3.8 months within the first 2 days of admission at the Dept. of Child Health, University of Benin. In comparison to the control group, the malnourished children showed a marked decrease of polyunsaturated FA with low linoleic acid, mainly in sterol esters (STE), and severely reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 55 publications
5
30
0
Order By: Relevance
“…Signi®cantly lower LA and AA values in malnourished children than in controls is a uniform ®nding in most studies, whereas plasma and erythrocyte membrane ALA values appear to be basically unaffected by PEM (Holman et al, 1981;Wolff et al, 1984;Koletzko et al, 1986;Vajreswari et al, 1990;Leichsenring et al, 1992). It is unclear whether the availability of DHA is affected: signi®cantly lower plasma phospholipid DHA values than in healthy controls were reported in Argentine (Holman et al, 1981) and Nigerian (Leichsenring et al, 1995) but not in another group of Nigerian (Koletzko et al, 1986) and in Sudanese (Leichsenring et al, 1992) malnourished children (Table 1).…”
Section: Metabolism Of Essential Fatty Acids In Malnourished Childrenmentioning
confidence: 90%
See 1 more Smart Citation
“…Signi®cantly lower LA and AA values in malnourished children than in controls is a uniform ®nding in most studies, whereas plasma and erythrocyte membrane ALA values appear to be basically unaffected by PEM (Holman et al, 1981;Wolff et al, 1984;Koletzko et al, 1986;Vajreswari et al, 1990;Leichsenring et al, 1992). It is unclear whether the availability of DHA is affected: signi®cantly lower plasma phospholipid DHA values than in healthy controls were reported in Argentine (Holman et al, 1981) and Nigerian (Leichsenring et al, 1995) but not in another group of Nigerian (Koletzko et al, 1986) and in Sudanese (Leichsenring et al, 1992) malnourished children (Table 1).…”
Section: Metabolism Of Essential Fatty Acids In Malnourished Childrenmentioning
confidence: 90%
“…To complicate matters, different effects on EFA metabolism of the two major forms of PEM, kwashiorkor and marasmus were reported in some (Vajreswari et al, 1990) but not in other (Koletzko et al, 1986) studies. (Vajreswari et al, 1990 reported subnormally low erythrocyte membrane lipid AA values in marasmic children, but not in children suffering from kwashiorkor.…”
Section: Metabolism Of Essential Fatty Acids In Malnourished Childrenmentioning
confidence: 99%
“…FA are also found in triglycerides, cholesterol esters and in free FA. The profile of FA in the various lipids is known to differ [2,21,22]. Accordingly, the total FA composition in serum is related to variations in FA metabolism as well as to the relation between the different lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Children with SAM have decreased desaturase activity, resulting in decreased synthesis of AA and DHA from their precursors (Koletzko et al 1986;). …”
Section: Discussionmentioning
confidence: 99%